Profiles of change in motivation for teaching in higher education at an American research university. Issue 6 (17th August 2016) - Gunersel, Adalet B.; Kaplan, Avi; Barnett, Pamela; Etienne, Mary; Ponnock, Annette R.
ABSTRACT: The current study employed an emergent theoretical model of teaching role identity and motivation to investigate the change in conception of and motivation for teaching in higher education of research graduate students who teach in the United States. Fifteen participants took a graduate-level seminar as part of a two-course teaching professional development (PD) program. Qualitative content analysis of the participants' pre-seminar and post-seminar reflective essays focused on change in the theoretical model's components – participants' goals, self-perceptions, epistemological beliefs, and action possibilities – and their alignment. The findings suggested four kinds of change in each component, ranging from dramatic change to reversed change, as well as three general profiles of change labeled 'Transformation, ' 'Elaboration', and 'Stagnation'. The model proved useful in conceptualizing the change in participants' teaching-related conceptions and motivation and could provide a guide for future research on teaching motivation and for designing and evaluating teaching PD in higher education.